MODEL PROGRAM STUDI ASURANSI SYARIAH FEBI UIN SU MEDAN DALAM MELAKUKAN PELAMPAUAN INDIKATOR KINERJA UTAMA - Tri Inda Fadhila Rahma; Rahmi Syahriza; Atika Atika (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to establish a model that can reflect how the Main Performance Indicators are exceeded, so that they can become IKT documents (Additional Performance Indicators) specifically for the Islamic Insurance Study Program at FEBI UIN SU Medan. The material used in this study is the main performance indicators and additional performance indicators from several universities in Indonesia. Main Performance Indicators (IKU) are measurements obtained from organizational performance by calculating indicators in fulfilling performance, especially in certain targets and goals, while Additional Performance Indicators (IKT) are governance, governance and other cooperation indicators developed by universities and/or UPPS and research programs to go beyond SN-DIKTI. In this study, it limits KPI and IKT in Education, Research and Service. The approach method used in this research is a descriptive qualitative method, which is a method for seeking information related to research subjects through interviews with stakeholders. The objects of this research are FEBI Managers of UIN SU Medan, namely leaders and lecturers who have the additional task load of managing FEBI UIN SU Medan, FEBI Students of UIN SU Medan in this case Sharia Insurance students and stakeholders, namely parties related to FEBI UIN SU Medan and have certain competencies, especially in terms of determining performance appraisal. The results of this study are that the Islamic Insurance Study Program has exceeded the determination of the Key Performance Indicators issued by SN-Dikti. In determining the Additional Performance Indicators for the Islamic Insurance Study Program, it is adjusted to the Strategic Plan (Renstra) of the Study Program derived through the Strategic Plan of UIN North Sumatra Medan and the Faculty of Islamic Economics and Business, UIN North Sumatra Medan. The Islamic Insurance Study Program sets educational standards to make license certificates (profession) from Financial Institutions such as Insurance a requirement for student graduation, on research standards that lecturer and student research refer to research themes set by the study program and community service standards that lecturers and students collaborate in carrying out PKM by adjusting the community service theme that has been set by the study program. So in determining the IKT, the Sharia Insurance study program has exceeded.